2000
DOI: 10.1097/00007632-200002150-00005
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Effects of Nerve Root Retraction on the Posterior Ramus

Abstract: Findings showed that posterior lumbar procedures, including retraction of paravertebral muscle, fenestration of the lamina, and retraction of the nerve root affect the posterior ramus. Excessive retraction of the nerve root has an especially disastrous effect on the posterior ramus. Such a violent maneuver within the spinal canal must be avoided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Nagayama and colleagues 2 demonstrated in rats that excessive retraction of lumbar nerve roots caused postoperative nerve root damage that could be observed in postoperative anatomical studies. 2 Matsui and colleagues 1 published a study of 31 patients undergoing lumbar discectomy; they described the intraoperative nerve root retraction pressure and corresponding perfusion of the compromised nerve root. The authors found that the length of time in which elevated nerve root pressure was applied produced an additional effect that increased postoperative neurological compromise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nagayama and colleagues 2 demonstrated in rats that excessive retraction of lumbar nerve roots caused postoperative nerve root damage that could be observed in postoperative anatomical studies. 2 Matsui and colleagues 1 published a study of 31 patients undergoing lumbar discectomy; they described the intraoperative nerve root retraction pressure and corresponding perfusion of the compromised nerve root. The authors found that the length of time in which elevated nerve root pressure was applied produced an additional effect that increased postoperative neurological compromise.…”
Section: Discussionmentioning
confidence: 99%
“…Of consequence, the "timed force" exerted against the involved nerve root as it is retracted during decompressive surgery has attracted considerable attention. [1][2][3]5 Our study was designed to focus on the dynamics of such retraction.…”
mentioning
confidence: 99%
“…Actually, the retraction injury of nerve roots and dura is a leading cause of the lower limb pain, numbness, weakness, and even the failure of back surgery [5][6][7]. Moreover, excessive retraction of the nerve root has an especially disastrous effect on the posterior ramus.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, excessive retraction of the nerve root has an especially disastrous effect on the posterior ramus. Thus, such a violent maneuver within the spinal canal must be avoided or reduced to the minimum [6], and how to avoid the intraoperative retraction injury is an important measure to assess the success of an intraspinal operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation